Membuka Toleransi Beragam Dalam Merajut Harmoni Sosial : Belajar Memanusiakan-Manusia Melalui Toleransi - Valensius Ngardi; Gratia Wing Artha (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Paramadina, 2025)
On the other hand, others are already striving to implement the values ​​inherent in us as citizens of Indonesian culture, such as egalitarianism, tolerance, and humanism, with interfaith dialogue that should adorn our daily lives with others. Furthermore, there is another view that the governance of religious diversity under the auspices of Pancasila and the 1945 Constitution does not guarantee the humane and wise recognition of religious rights regarding one's beliefs in the public sphere. Minority rights are often ignored due to the influence of various interests in identity politics, power relations, and hegemonic leadership. Each citizen still understands tolerance as merely discourse and an idea. In dialogue spaces, the implementation of a culture of tolerance becomes a heated discussion, although in certain areas, people can still coexist within the framework of differing beliefs. Identity politics is increasingly strengthened when relations between religious communities are fraught with group mapping based on identity, race, ethnicity, and religion. This simple article is merely a reflection aimed at presenting harmony of tolerance as a social control to prevent ripples of intolerance issues in Indonesia as the author's reflection on cases that touch on religion through various approaches. Three approaches: Power, Rights, & Interests, according to Samsu Rizal Panggabean, are a strong foundation in finding a space for togetherness and religious differences in Indonesia. For the case in this article, the author takes a power approach. This is also supported by Bhiku Parekh on the theory of religious tolerance in the context of multiculturalism. In addition, in the study of religious phenomenology, it is supported by Jacques Waardenburg's view of three urgent needs in studying Muslim-Christian relations as a fundamental framework by unraveling the problems of religious conflict that occur in Indonesian society today.